Penerapan Balanced Scorecard Guna Meningkatkan Kinerja Polda Jatim - Eka Fitriandari; Pompong Budi Setiadi; Sri Rahayu (Departement of Mathematics Education, 2023)
while the East Java Regional Police, which is referred to as the East Java Regional Police, is the executor of duties and the authority of the Indonesian National Police in the area of East Java Province which is under the National Police Chief. By prioritizing the Vision and Mission of the East Java Regional Police, to optimize better public services (towards the excellent stage) internal business processes and external outcomes are needed in order to improve performance and strategic achievements in a sustainable manner in action. To measure and improve the performance of the public sector, it is necessary to choose a comprehensive performance measurement technique, namely the Balanced Scorecard, so that it can be used by public sector organizations, the Balanced Scorecard needs to be modified. This study aims to understand and examine the application of the balanced scorecard as a performance measurement tool. The method used in this research is descriptive qualitative. The steps taken in this research are collecting, classifying, presenting, and processing data. After that, make a systematic, accurate, and factual description of the facts of the object under study. This research uses the East Java Regional Police Performance Report for 2021, with innovative developments in the application of a performance measurement system that can be implemented by work units. The results of the study show a summary of perspectives into three namely the stakeholder or customer perspective, internal business processes and learning and growth perspective. It can be concluded that the implementation of the balanced scorecard as a whole is good as indicated by the determination of the perspective and achievement of the Key Performance Indicators (IKU), which have been aligned with the organizational strategy and its implementation encourage the achievement of performance targets so that it encourages improvement and better performance improvement in the future.